Irmédi-Molnár Lászlóhoz (Fodor Ferenc gyászjelentése) - Fodor Ferencné (Fond 165 Irmédi-Molnár László, 1962)
Fond 165 Irmédi-Molnár László > Irmédi-Molnár László iratai. > Irmédi-Molnár László levelezése. > Irmédi-Molnár Lászlóhoz írott levelek.